2017
DOI: 10.1038/s41598-017-10983-x
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB2 is a novel TGFβ-responsive lineage fate determinant of human bone marrow stromal cells

Abstract: TGF-β1, a multifunctional regulator of cell growth and differentiation, is the most abundant bone matrix growth factor. During differentiation of human bone stromal cells (hBMSCs), which constitute bone marrow osteoblast (OS) and adipocyte (AD) progenitor cells, continuous TGF-β1 (10 ng/ml) treatment enhanced OS differentiation as evidenced by increased mineralised matrix production. Conversely, pulsed TGF-β1 administration during the commitment phase increased mature lipid-filled adipocyte numbers. Global gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Recent studies have showed that TGF-β promoted adipocyte commitment. The difference was that they studied the adipocyte commitment of BMSCs isolated from different species: mice and humans [45,47]. MSC origin may affect adipocyte commitment under TGF-β signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have showed that TGF-β promoted adipocyte commitment. The difference was that they studied the adipocyte commitment of BMSCs isolated from different species: mice and humans [45,47]. MSC origin may affect adipocyte commitment under TGF-β signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies have reported that TGF-β suppresses the adipocyte commitment of MSCs, recent studies showed that TGF-β promotes adipocyte commitment. A single pulse dose treatment with TGF-β during the commitment phase led to increased adipogenesis of human BMSCs, while continuous treatment during the whole phase (commitment phase and differentiation phase) inhibited adipogenesis [47]. The reason could be TGF-β promoted the first step adipocyte commitment, but inhibited the second step adipogenic differentiation of BMSCs by repressing the function of C/EBPβ and C/EBPδ during the differentiation phase [68].…”
Section: Tgf-β Signaling In the Adipocyte Commitment Of Mscsmentioning
confidence: 99%
“…Transforming growth factor beta 1 is the most abundant growth factor in bone matrix and regulates cell growth and differentiation. Human bone marrow mesenchymal stromal/stem cells (BM-MSCs) treated with TGF-β1 for up to 7 days, showed reduced adipogenic differentiation in favour of osteogenic differentiation [55]. Global gene expression analysis revealed that serpin peptidase inhibitor clade B (ovalbumin) member 2 (SERPINB2) was significantly downregulated in TGF-β1 treated cells.…”
Section: Tgf-β Signallingmentioning
confidence: 99%
“…Not completely immortalized because E6/E7 was sufficient to extend lifespan but not to bypass senescence 4. Probably incompletely immortalized 5 [30,68,69]. employed hMSC-hTERT-derived clones.…”
mentioning
confidence: 99%